Introducing carbon taxes at member state level: Issues and barriers - Stefan E. Weishaar (Austrian Institute of Economic Research (WIFO), 2018)
This paper examines the implementation issues and barriers for introducing a carbon tax at EU member state level. Important success determinants are related to the political economy of introducing taxes (negotiations with stakeholders, concessions, changes in proposed legislation, compromises, etc.) which translate i.a. into competitiveness issues, and fairness/equity/distribution issues. For these the design of the carbon tax exemptions, and safeguards to prevent progressivity and the use of the tax proceeds are important. The analysis will focus on the "frontrunner" countries in the EU which have been very successful in terms of the introduction of carbon taxes (Sweden, Denmark and Finland). The countries employed different implementation strategies but underscore the importance of successful issue, timing, linking and to foster political support by safeguarding competitiveness and by addressing income distributions.
Keywords: H23; K34; 330; Carbon taxes; Climate change